2022
DOI: 10.3389/fpsyg.2022.762993
|View full text |Cite
|
Sign up to set email alerts
|

Affect and Cognition in Managerial Decision Making: A Systematic Literature Review of Neuroscience Evidence

Abstract: How do affect and cognition interact in managerial decision making? Over the last decades, scholars have investigated how managers make decisions. However, what remains largely unknown is the interplay of affective states and cognition during the decision-making process. We offer a systematization of the contributions produced on the role of affect and cognition in managerial decision making by considering the recent cross-fertilization of management studies with the neuroscience domain. We implement a Systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 116 publications
(183 reference statements)
1
9
0
Order By: Relevance
“…Our analysis confirms that affect, as evidenced by the fluctuations of PP activation due to market fluctuations or financial transactions, plays a prominent role in the financial risk processing and decision making process for professional traders in their daily trading activities [ 18 ]. Our results provide contextual support for the growing literature of affective science investigating the relations between emotions and decision making [ 38 – 40 ] in the case of professional traders, whose profession requires them to make rational decisions under large uncertainties and maximize their payoffs.…”
Section: Discussionsupporting
confidence: 76%
“…Our analysis confirms that affect, as evidenced by the fluctuations of PP activation due to market fluctuations or financial transactions, plays a prominent role in the financial risk processing and decision making process for professional traders in their daily trading activities [ 18 ]. Our results provide contextual support for the growing literature of affective science investigating the relations between emotions and decision making [ 38 – 40 ] in the case of professional traders, whose profession requires them to make rational decisions under large uncertainties and maximize their payoffs.…”
Section: Discussionsupporting
confidence: 76%
“…We cannot make any conclusions about their evolution from our data but at the point they reach unicorn valuation, we provide conclusive evidence about how they behave. A recent systematic literature review answering the research question of how affect and cognition interact in managerial decision making found that there are alternative schools of thought on whether affective reasoning, cognitive reasoning, or a combination of these dominates managerial decisions (Cristofaro et al, 2022b). The authors conclude that the two systems work together, and that affective reasoning plays an initial role in driving the cognitive state in managerial decision-making.…”
Section: Strategies Of Unicornsmentioning
confidence: 99%
“…About the latter, the neurostrategy approach to management seeks to answer unexplored questions concerning the study of the human rationality of management decision-makers by finding connections between mental constructs with the activation of particular areas of the brain (Powell, 2011). Despite already recognized methodological drawbacks of neurostrategy research (Cristofaro, 2021; Cristofaro et al , 2022), the interconnection with behavioral strategy is needed, and giving this latter a driving role is even more important to orient neuroscience evidence toward a useful theory and practice.…”
Section: The Future Of Behavioral Strategy Studiesmentioning
confidence: 99%